2002
DOI: 10.1016/s0370-2693(02)01909-3
|View full text |Cite
|
Sign up to set email alerts
|

On the dependence of the gauge-invariant field-strength correlators in QCD on the shape of the Schwinger string

Abstract: We study, by numerical simulations on a lattice, the dependence of the gauge-invariant two-point field-strength correlators in QCD on the path used to perform the color parallel transport between the two points. (PACS code: 12.38.Gc) *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…In Appendix C, we have also demonstrated that, in accordance with the lattice results of Ref. [115], the correlation length of nonperturbative-nonconfining interactions of the background fields decreases with the deformation of the path interconnecting the two points in the correlation function (120). Finally, as has been announced at the beginning of this Section, let us discuss a possible modification of the 4D dual Abelian Higgs model, which can allow for the existence of different correlation lengths of the functions D(x) and D 1 (x).…”
Section: Correlation Lengths Of the Stochastic Yang-mills Fieldssupporting
confidence: 89%
See 4 more Smart Citations
“…In Appendix C, we have also demonstrated that, in accordance with the lattice results of Ref. [115], the correlation length of nonperturbative-nonconfining interactions of the background fields decreases with the deformation of the path interconnecting the two points in the correlation function (120). Finally, as has been announced at the beginning of this Section, let us discuss a possible modification of the 4D dual Abelian Higgs model, which can allow for the existence of different correlation lengths of the functions D(x) and D 1 (x).…”
Section: Correlation Lengths Of the Stochastic Yang-mills Fieldssupporting
confidence: 89%
“…This calculation allows us to show that the correlation length of nonperturbative-nonconfining self-interactions of the background fields decreases with the deformation of that trajectory, in agreement with the lattice results of Ref. [115].…”
Section: Correlation Lengths Of the Stochastic Yang-mills Fieldssupporting
confidence: 89%
See 3 more Smart Citations